peN-, ter-, dan meN- PENGARUH PENGGUNAAN METODE SQ3R (SURVEY, QUESTION, READ, RECITE, REVIEW) TERHADAP MEMBACA DAN MENULIS SISWA KELAS III DI SD NEGERI 03 SUKAMAJU: Penerapan Metode SQ3R dalam Pembelajaran Membaca dan Menulis - Megasari, Rini (PENA KREATIF : JURNAL PENDIDIKAN, 2026)
This study aims to examine the effect of the SQ3R (Survey, Question, Read, Recite, Review) method on the reading and writing skills of third-grade students at SD Negeri 03 Sukamaju. Low basic literacy skills and the limitations of conventional methods motivated this quasi-experimental study. A nonequivalent control group design was used, involving 21 students divided into experimental and control groups. The research instrument, a reading comprehension and writing test, was analyzed using an independent sample t-test. The results showed a significant difference in improvement between the two groups, with a normalized N-Gain value of 0.63 for the experimental group (medium-high category) and 0.30 for the control group. The statistical analysis yielded a significance value of 0.000 (p < 0.05). Thus, it can be concluded that the SQ3R method has a positive and significant effect on improving students' reading and writing skills. This method is recommended as a structured alternative learning strategy to address literacy challenges in elementary schools.